Modal filtered-x LMS algorithm for global active noise control in a vibro-acoustic cavity - Puri, Amrita; Modak, Subodh V.; Gupta, Kshitij (Mechanical systems and signal processing, 2018)
•An algorithm named as 'Modal filtered-x LMS algorithm' proposed for global active noise control.•Filtered-x LMS algorithm is formulated in the modal domain to reduce acoustic potential energy.•Concepts of 'modal secondary paths' and ‘modal filtered reference signals’ are introduced.•A numerical study presented to reduce noise in a car-like vibro-acoustic cavity.•Contributions of specific or chosen modes to the acoustic potential energy can be reduced.•The method offers computational advantage over the conventional method for global ANC. This paper proposes an algorithm called as 'Modal filtered-x LMS algorithm' for global active noise control in vibro-acoustic cavities. The proposed algorithm is a formulation of the conventional filtered-x least mean square algorithm in modal domain to reduce acoustic potential energy in a cavity. The formulation leads to a concept of what has been called as 'modal secondary path' in the paper. The active control method makes use of the reference signal filtered using modal secondary paths instead of the reference signal filtered using physical secondary paths as done in the conventional FxLMS algorithm. The method requires knowledge of acoustic modal pressures which in the present paper are estimated using acoustic pressure measurements at a discrete number of points in the cavity. The proposed method allows a modal based control of acoustic potential energy in the cavity. The proposed method also has an advantage that it reduces the computational burden associated with filtering of the reference signal with secondary paths for global control. A numerical study to actively control noise due to structural and acoustic disturbances acting on a car-like cavity is presented. Results of modal based control are compared with maximum reduction that is possible for given disturbances and control sources. It is found that the noise reduction obtained using the modal based approach is close to the maximum possible but at a lower computational cost.